Appalachia Has Got Talent, But Why Does It Flow Away? A Study on the Determinants of Brain Drain From Rural USA. Issue 3 (August 2019) - Vazzana, Caryn M.; Rudi-Polloshka, Jeta
This study contributes to the understanding of factors that affect brain drain from Central Appalachia. Using empirical methods, the authors analyze a unique data set from a survey of Appalachian students studying at a higher education institution located in Central Appalachia. A higher perceived likelihood of finding an interesting job with attributes such as a good salary and advancement opportunities, is by far the most important factor influencing students' intentions to stay in Appalachia. Furthermore, students who perceive a higher likelihood of having job opportunities for their spouse or partner, as well as opportunities to advance their education in the Appalachian region, also report a higher likelihood of staying in the region upon graduation. This analysis provides further evidence that the strongest pull factor in keeping talent in the Appalachian region of the United States is creating public–private partnerships to provide more job opportunities to young educated people.